Portrait of William Henry Perkin (1838-1907) (1906)
Portrait of William Henry Perkin (1838-1907). Known as the father of the synthetic chemical industry, Perkin created the first synthetic dye, mauveine, in 1856, while attempting to create an artificial version of the drug quinine. Perkin’s mauve became the first commercially available mass-produced dye and paved the way for other notable synthetic dyes, including fuchsin (1858), ceruleine (1871), and synthetic indigo (1880).
Keywords: Portrait photography; Dyes and dyeing; Portraits; Perkin, William Henry, Sir, 1838-1907